DESKRIPSI PEMAHAMAN KONSEPTUAL DAN KELANCARAN PROSEDURAL MATERI PTLSV DITINJAU DARI GAYA BELAJAR SISWA PONDOK PESANTREN - Badaruddin, Badaruddin; Hartoyo, Agung; Suratman, Dede (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to explain conceptual understanding and procedural fluency in terms of student learning style on linear inequality material one variable. The method that was use in this research is descriptive method with case study form. There were 34 students participated in class VII SMP Darut Tauhid Kubu Raya as the subject in this research. The instrument of data collecting are written test to reveal the conceptual understanding and procedural fluency, questionnaire to categorize the students based on their learning style and interview as the followup activity. The results of the data analysis show that conceptual understanding in students who have visual learning style and kinesthetic learning style included in medium category, whereas in auditory learning style include in low category. Procedural fluency in all of students who have visual learning style, auditory learning style and kinesthetic learning style included in very low categories.Keyword : Conceptual Understanding, Procedural Fluency, Learning Style